Regenerative potential of immune cells after traumatic muscle injury - Pu, Su; Hu, Guangmin; Cao, Yulu; Shen, Guoming; Wang, Yuqing (Frontiers in Immunology, 2025)
Traumatic muscle injury (TMI) causes significant morbidity and socioeconomic burden. Immune cells are central to the subsequent regenerative response, orchestrating dynamic interactions between innate and adaptive immunity. This review systematically summarizes the current understanding of the roles of key immune cells (neutrophils, macrophages, eosinophils, basophils, T lymphocytes, B lymphocytes) in TMI pathophysiology and repair, based on a comprehensive analysis of recent literature. Their intrinsic mechanisms, contributions to tissue regeneration, and therapeutic implications are discussed. Furthermore, we explore therapeutic strategies targeting immune cells, including biomaterials, pharmacologic interventions, cell therapies, and physical modalities. The aim of this review is to provide a consolidated understanding of immune-mediated repair mechanisms in TMI and to identify critical knowledge gaps and future research directions necessary for developing novel immunomodulatory therapies to optimize muscle regeneration and functional recovery.